Tidal‐induced net transport effects on the oxygen distribution in the thermosphere. Issue 14 (24th July 2014) - Jones, M.; Forbes, J. M.; Hagan, M. E.
Abstract Through a series of numerical experiments performed with the National Center for Atmospheric Research Thermosphere‐Ionosphere‐Mesosphere‐Electrodynamics General Circulation Model, we evaluate a new mechanism by which the dissipation of vertically propagating tides acts to change the O distribution in the thermosphere. Jones et al. (2014) proposed that the tides induced a net transport of constituents themselves, in addition to the transport provided by the mean circulation induced by the dissipation of tides. Through diagnosis of the continuity equation for [O], our results show that the net meridional and vertical transport of O induced by the tides appreciably contributes to [O] changes in the lower thermosphere. Combined with recombination, these transport mechanisms drive a net reduction in [O] of ∼25% that is transmitted to higher altitudes by molecular diffusion. The migrating diurnal tide appears to be the main driver of the [O] variations during September.